High Risk Posture on Motor-Manual Short Wood Logging System in Acacia mangium Plantation - Efi Yuliati Yovi; Widya Prajawati (Institut Pertanian Bogor (IPB University), 2015)
Motor-manual logging has been considered as the most dominant logging system in Java Island, Indonesia. The system-which consisted of felling, delimbing, bucking, hauling, and transporting activities- involves a combination of stress factors e.q. difficult work postures, generation of force, and lifting techniques. In the other hand, combination of the three is well associated with high risk of work-related musculoskeletal injuries (MSIs), including musculoskeletal disorders. This research aimed to assess difficult work posture on felling, delimbing, bucking, and manually short wood hauling by employing rapid entire body assessment (REBA) technique and muscular pain scoring based on the worker's perceive. It was revealed that felling and manual hauling were scored 4 in the REBA action level, indicated very high MSIs risk level, and categorized as “necessary now” for an injury risk preventive action. The workers' pain scoring indicated that low back (spine in general) disorders resulting in low back pain has been considered to be the one of the leading safety issues in the felling and manual hauling. Regardless to complex mechanism of how the personal risk and environmental factors associated with manual material handling injuries, job-related factors approach should be underlined in the MSIs prevention initiative in motor-manual logging.